2016
DOI: 10.18632/oncotarget.12885
|View full text |Cite
|
Sign up to set email alerts
|

The changing characteristics and molecular profiles of papillary thyroid carcinoma over time: a systematic review

Abstract: BackgroundThe genetic alterations of papillary thyroid carcinoma (PTC) have been reported to change over the past few decades. We performed this systematic review to further examine the trends and modifications of patient demographic, clinicopathological features and molecular profiles of PTC over time.MethodsA literature search was performed within six electronic databases to identify relevant articles. The inclusion criteria were published studies investigating BRAF mutations, RET/PTC rearrangements or RAS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 52 publications
2
44
0
5
Order By: Relevance
“…Elisei et al (30) suggested that iodine supplementation might be associated with the increasing trend of BRAF mutation in PC. The frequency of BRAF mutations reported in the literature has increased significantly over the years (31). This may be related to innovations in methodologies used to detect mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elisei et al (30) suggested that iodine supplementation might be associated with the increasing trend of BRAF mutation in PC. The frequency of BRAF mutations reported in the literature has increased significantly over the years (31). This may be related to innovations in methodologies used to detect mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the detection sensitivity of NGS reported in previous studies is >94% (40), which is greater than that of SGS. Results from numerous studies and meta-analyses have associated the BRAF V600E mutation with high-risk clinicopathologic features, such as larger tumor size, extrathyroidal extension, higher stage at presentation, and lymph node and distant metastases in patients with PC (4,20,22,30,31,(41)(42)(43). However, these associations remain controversial.…”
Section: Pathologic Findingsmentioning
confidence: 99%
“…The incidence of thyroid cancers is rapidly increasing [1] with a projected prevalence of about 5539 cases in the year 2017. The major histological types of thyroid cancers are papillary, follicular, medullary and anaplastic thyroid cancers.…”
Section: Clinical Utility Of Immunohistochemistry Using the Novel Antmentioning
confidence: 99%
“…62 It was reported that TC was steadily increasing in morbidity and mortality over the years. According to epidemiological data, the incidence of TC has been increased by an average of 4.5% per year from 2007 to 2011 in the United States.…”
Section: Thyroid Cancermentioning
confidence: 99%